Benefits and challenges of knowledge management in public sector : a case study of local authorities in Malaysia / Kalsom Salleh, Syed Noh Syed Ahmad and Syed Omar Sharifuddin Syed Ikhsan - Salleh, Kalsom; Syed Ahmad, Syed Noh; Syed Ikhsan, Syed Omar Sharifuddin (Research Management Institute (RMI), 2010)
The potential impact of knowledge management in the public sector organizations on the stakeholders is greater than that in the private sector organizations. Knowledge management is regarded as an essential component to the Electronic Government evolution in Malaysia because it uses people and technology to generate creativity and innovation in the existing systems to improve productivity and quality of services. Thus. this paper explores the role ofknowledge management in the Local Authorities in a broader perspective towards achieving the Electronic Government. A case study research of knowledge management in the Local Authorities is imperative as it provides empirical evidence on whether knowledge management is a suitable platform for Electronic Government evolution in Malaysia. Survey questionnaires were distributed to the senior and middle management government officers in the Local Authorities located in the Kuala Lumpur Federal Territory and Selangor State. This group ofgovernment officers was selected as they are responsible for the strategic policies and operational management in various departments ofthe Local Authorities. The responses from the questionnaires were aimed to identify the potential benefits and challenges in using KM as a strategic management tool to improve the internal operational efficiency and electronic service delivery system ofthe Local Authorities. Thefindings revealed a high level ofperceived importance ofKM benefits in achieving the Electronic Government paradigm. However, the main obstaclesfor the Local Authorities to adopt knowledge management are non-standardized processes and procedures of organizational systems and outdated information and communication technology and inadequate knowledge management tools.